Environmental heat stress induces epigenetic transgenerational inheritance of robustness in parthenogenetic Artemia model. Issue 8 (22nd April 2014) - Norouzitallab, Parisa; Baruah, Kartik; Vandegehuchte, Michiel; Van Stappen, Gilbert; Catania, Francesco; Bussche, Julie Vanden; Vanhaecke, Lynn; Sorgeloos, Patrick; Bossier, Peter
Abstract : The notion that phenotypic traits emerging from environmental experiences are heritable remains under debate. However, the recent report of nonmendelian transgenerational epigenetic inheritance, i.e., the inheritance of traits not determined by the DNA sequence, might make such a phenomenon plausible. In our study, by carrying out common garden experiments, we could provide clear evidences that, on exposure to nonlethal heat shocks, a parental population of parthenogenetic (all female) Artemia (originating from one single female) experiences an increase in levels of Hsp70 production, tolerance toward lethal heat stress, and resistance against pathogenic Vibrio campbellii . Interestingly, these acquired phenotypic traits were transmitted to three successive generations, none of which were exposed to the parental stressor. This transgenerational inheritance of the acquired traits was associated with altered levels of global DNA methylation and acetylated histones H3 and H4 in the heat‐shocked group compared to the control group, where both the parental and successive generations were reared at standard temperature. These results indicated that epigenetic mechanisms, such as global DNA methylation and histones H3 and H4 acetylation, have particular dynamics that are crucial in the heritability of the acquired adaptive phenotypic traits across generations.—Norouzitallab, P., Baruah, K., Vandegehuchte, M., Van Stappen, G., Catania, F., Vanden Bussche, J., Vanhaecke, L., Sorgeloos, P., Bossier, P. Environmental heat stress induces epigenetic transgenerational inheritance of robustness in parthenogenetic Artemia model. FASEB J. 28, 3552–3563 (2014). www.fasebj.org